Aplikasi Monitoring Pegawai ASN Kelurahan Pademangan Timur - Rafih, Muhammad; Malabay (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
This study aims to design, develop, and test an Android-based monitoring application for Civil Servants (ASN) in Kelurahan Pademangan Timur using the prototypemethod. The background of the study highlights the need for an effective system for managing ASN performance at the village level and the lack of research focusing on similar applications at this level. The problem identification points to the absence of an integrated system, limited information accessibility, lack of transparency, insufficient use of information technology, and gaps in previous research. This study produces an application that enables effective monitoring and management of ASN performance, with benefits such as increased efficiency, transparency, user satisfaction, and contributions to the development of information technology in the public sector. The results of this study are expected to provide a reference for the development of similar applications in other regions of Indonesia.